2023
DOI: 10.1590/1678-7757-2022-0359
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease severity is associated to pathogenic consortia comprising putative and candidate periodontal pathogens

Abstract: Periodontal disease severity is associated to pathogenic consortia comprising putative and candidate periodontal pathogens * Based on a holistic concept of polymicrobial etiology, we have hypothesized that putative and candidate periodontal pathogens are more frequently detected in consortia than alone in advanced forms of periodontal diseases (PD). Objective: To correlate specific consortia of periodontal pathogens with clinical periodontal status and severity of periodontitis. Methodology: Subgingival biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…In recent studies, other species, such as Filifactor allocis, have been investigated as putative new pathogens, and a clinical investigation confirmed their presence in patients with periodontitis [26]. These results suggest that the composition of the biofilm associated with periodontal disease may be more complex and diverse than previously thought [27,28]. In this context, it has been shown that a consortium of bacteria, rather than a single species, is accountable for the transition of the biofilm from a state associated with oral health to one that is pathogenic.…”
Section: Discussionmentioning
confidence: 84%
“…In recent studies, other species, such as Filifactor allocis, have been investigated as putative new pathogens, and a clinical investigation confirmed their presence in patients with periodontitis [26]. These results suggest that the composition of the biofilm associated with periodontal disease may be more complex and diverse than previously thought [27,28]. In this context, it has been shown that a consortium of bacteria, rather than a single species, is accountable for the transition of the biofilm from a state associated with oral health to one that is pathogenic.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding periodontal disease, the implication of F. alocis in periodontal disease severity is well-described in clinical studies. 32 , 33 Moreover, previous research has pointed out a potential role in periodontal disease pathogenesis for some species detected in the subgingival biofilm that are not usually associated with periodontal diseases, such as Acinetobacter baumannii and Pseudomonas aeruginosa . 34 , 35 However, few studies explore the role of these bacteria and other “non-periodontal” species in peri-implant health or peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
“… 9 P. gingivalis and its virulence factors have been extensively studied in consortium with other species characterizing a polymicrobial synergy, 18 which is directly associated to alveolar bone loss. 19 In this aspect, many cell types are important to orchestrate tissue response and bridge the link to the overall systemic health, including antigen-presenting cells, 20 T cells, 21 , 22 and architectural stromal cells, which can assume an immune phenotype and function on demand. 23 …”
Section: Periodontitis: An Age-related Infection-driven and Immune-me...mentioning
confidence: 99%